2018
DOI: 10.1093/jee/toy217
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Four Hermetic Bag Brands Against Prostephanus truncatus (Coleoptera: Bostrichidae) in Stored Maize Grain

Abstract: Hermetic storage technology using plastic liners is threatened by the boring action of Prostephanus truncatus Horn. (Coleoptera: Bostrichidae), a major insect pest of stored maize in sub-Saharan Africa. We investigated the performance of four brands of hermetic storage bags against adult P. truncatus in maize stored for 90 d under simulated resident and incoming infestation. Five treatments were used: four hermetic bag brands; SuperGrain Bag (SGB) IV-R, SGB Farm, Purdue Improved Crop Storage (PICS) bag, and Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The increase in insect populations and damages to grain stored in ZeroFly ® and control woven bags observed here corroborates findings of previous studies in which maize was stored in several different countries in sub-Saharan Africa [ 19 , 25 , 27 , 28 , 29 ]. The present study further confirmed that C. maculatus is the only insect species that attacks cowpea during storage in West Africa.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The increase in insect populations and damages to grain stored in ZeroFly ® and control woven bags observed here corroborates findings of previous studies in which maize was stored in several different countries in sub-Saharan Africa [ 19 , 25 , 27 , 28 , 29 ]. The present study further confirmed that C. maculatus is the only insect species that attacks cowpea during storage in West Africa.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are corroborated by findings from other studies on maize in several regions of sub-Saharan Africa. These studies showed weigh losses ranging from 3% to 35% [ 19 , 20 , 22 , 25 , 27 , 28 , 29 ]. Our results contradict laboratory studies conducted in both Ghana and Nigeria that claimed 100% insect mortality and no weight loss of cowpea stored in 5 and 10 kg ZeroFly ® storage bags for 21 to 25 days [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A side-by-side experiment comparing PICS™ and SuperGrainbag™ for storing cowpea in Niger found no difference in effectiveness between the two hermetic bags [ 30 ]. Additional studies comparing several hermetic bags for controlling Prostephanus truncatus (Horn, Coleoptera: Bostrichidae) on stored maize in Malawi, Tanzania, and Zimbabwe found no difference among these technologies [ 22 , 28 , 31 ]. These hermetic bags are as effective as and often better than insecticides in protecting grains against insect attacks during storage [ 24 , 27 , 32 ].…”
Section: Introductionmentioning
confidence: 99%